FAKTOR - FAKTOR YANG MEMPENGARUHI KEBIJAKAN HUTANG PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ratna Meylani, 12.05.52.0163; Lisiantara, Anggana (Students Journal of Accounting and Banking, 2016)
This study examined of the factors affecting the debt policy in manufacturing companies. This research was conducted at the Indonesian Stock Exchange by using analysis of manufacturing companies. The sampling method using purposive sampling with the period from 2011 through 2014. The relationship between variables and or described by using multiple regression analysis. The results showed that managerial ownership , dividend policy, profitability and no significant negative effect on the debt policy. While the institutional ownership variable has a significant negative effect on debt policy and asset structure and no significant positive effect on debt policy. The variable size of the company s growth and positive and significant impact on the debt policy. Keywords: Manajerial Ownership, Institutional Ownership, Dividend Policy, Asset Structure, Profitability, Growth Company, Company Size, Debt Policy